Effect of thermo-mechanical treatments on nano-structure of 9Cr-ODS steel. (December 2016) - Oka, Hiroshi; Tanno, Takashi; Ohtsuka, Satoshi; Yano, Yasuhide; Uwaba, Tomoyuki; Kaito, Takeji; Ohnuma, Masato
Highlights: The oxide dispersion strengthened steel was composed of a fine-grained residual ferrite phase and a transformable martensite phase. The number density of nano particles in the residual ferrite phase was higher than that in the martensite phase. The thermo-mechanical treatments reduced the volume fraction of the residual ferrite phase, leading to the reduction of the total number density of nano-sized particles. Abstract: The effect of thermo-mechanical treatments (TMTs) on the evolution of nano-structure in an oxide dispersion strengthened (ODS) ferritic/martensitic steel (Fe-9Cr-2W-0.22Ti-0.36Y2 O3 ) was investigated. TMTs involve hot extruding and subsequent forging, which are expected to be part of a future industrial-scale manufacturing process of the ODS steel. It was shown that the ODS steel was composed of two phases — a fine-grained residual ferrite phase and a transformable martensite phase. The number density of the nano-sized particles in the residual ferrite phase was significantly higher than that in the martensite phase. The TMTs did not significantly affect the number density, but slightly affected the size distribution of the nano-sized particles in both ferrite phase and martensite phase. Moreover, the volume fraction of the residual ferrite phase decreased after TMTs. In summary, the TMT conditions could be a parameter which affects the nano-structure of the ODS steel.